Designation of the lectotype of Poecilia amazonica Garman, 1895 (Cyprinodontiformes, Poeciliidae) and discussion of its nomenclatural status - Lucinda, Paulo H. F.; Figueiredo, Carlos A.; Hartel, Karsten E. (Zootaxa, 2011)
Poecilia amazonica Garman, 1895 was described based on syntypes collected at Santa Cruz, Pará, Brazil by Mr. Caleb Cooke in October 1859. The type-series was originally deposited at the Museum of Comparative Zoology at Harvard University, under the catalog numbers MCZ 27573 (128 ex.), and MCZ 69635 (97 ex.). Five specimens were subsequently transferred to University of Michigan Museum of Zoology (UMMZ 146750), and six specimens were sent to the National Museum of Natural History (USNM 120286). Carl Hubbs examined parts of the type-series and considered the syntypes to be Micropoecilia parae (Eigenmann, 1894), as inferred from label information handwritten by Hubbs in 1944 and placed inside the jars of lots MCZ 27573 and UMMZ 146750 (ex MCZ 27573). However, Hubbs did not publish anything concerning the nomenclatural status of P. amazonica. Consequently, the name Poecilia amazonica has been considered valid by several authors since Garman’s description (e.g. Rosen & Bailey, 1963; Meyer, 1993; Rodriguez, 1997; Parenti et al., 1999; Lucinda, 2003; and Lucinda & Reis, 2005).